Analisis Hiperrealitas pada Film Aquaman sebagai Komoditas Kekuatan Kapitalis - Maulina Puspa Dewi; Liya Umaroh (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2022)
Film has the power to construct a person through the symbols it sends in each scene. In addition to the construction of meaning, film also has the power to fold and manipulate reality into nothing more than a narrow screen. This is known as hyperreality. Aquaman is a DC fantasy film that tells the story of the perfection of the hyperreal world of Atlantis. This study aims to analyze the hyperreality in the Aquaman film in order to build awareness that the visualization of the world of Atlantis is a commodity by capitalist forces. The researcher used a qualitative method with Roland Barthes' Semiotics analysis technique. The theory in this study uses the Theory of Simulacra and Hyperreality by Jean Baudrillard. Barthes' semiotics is used to observe the entire content of the film and analyze the meaning of denotation, connotation, and myth to find out its suitability with Baudrillard's thinking. The results show that this film is closely related to the concept of hyperreality which has passed through a series of 4 imaging phases. Hyperreality in the Aquaman film refers to everything that is